Plasma motilin, gastrin, and enteroglucagon and feeding in the human newborn. Issue 9 (September 1980) - Lucas, A; Adrian, T E; Christofides, N; Bloom, S R; Aynsley-Green, A
Abstract : Plasma concentrations of motilin, gastrin, and enteroglucagon were measured in cord blood and during the first 24 days of life before feeding in 45 term and 63 preterm, healthy infants. Levels of these hormones rose steeply after birth, reaching concentrations that were much higher than those in fasting adults. These increases in hormone concentration were not present in a group of 10 preterm infants who had received only intravaenous dextrose from birth because of hyaline membrane disease. Our findings suggest that early enteral feeding may trigger the postnatal increase in plasma concentrations of gut hormones and that this could play an important role in the physiologaical adaptations to extrauterine nutrition.